A study on defect rate of packaging in manufacturing company - Noor Hamidah, Mohd Thahir (2014)
This research is a study on defect rate of packaging in manufacturing company. The aims of this research are to identify the factor that contributed in the packaging defect at a manufacturing company and to give the suggestion to solve the problem of packaging defect. This research is a case study and was performed at one of the manufacturing company that produces spices and conducts the process of packaging at Indera Mahkota, Kuantan, Pahang. Data are obtained from the observation, interview and data collection at the manufacturing company. The data and the interview feedback will be analyzed by using the Minitab software and used the method of Pareto diagram and Cause and Effect diagram. The result shows that the manpower is the major factor that contributed to the packaging defect to this company. The results from this study can help the company to know the root cause of the problem and to reduce the defect from the factor that has been found